Ethical reflection for medical electives. (10th May 2017) - Tiller, Rose; Jones, June
Summary: Background: Forty per cent of UK medical students undertake their elective in a developing country. Although these opportunities are often rewarding, students encounter ethical questions, both in preparation and undertaking these projects. The British Medical Association highlights three key ethical considerations for elective students: clinical challenges, cultural challenges and impact on the host institution. This report reflects on these considerations in the context of a 4‐week medical elective conducted by UK medical students in the Solomon Islands. Methods: Daily interviews were conducted with a focus group of six medical students in the Solomon Islands over a 4‐week elective period. Descriptive analysis identified key themes. Findings: Students were aware of guidelines stating that they must act within their competency, but found it difficult to assess their own skills and capacities in unfamiliar non‐UK settings. Culturally different societal and medical norms proved particularly challenging. The impact of the student elective on the host hospital was also larger than anticipated. Discussion: In UK medical education, formal assessment sets the benchmark for competency. Assessments cannot cover every situation encountered on elective, and so students must therefore develop an alternative benchmark to measure their ability. The lack of research into the impact of electives on host institutions makes assessing the ethical nature of electives challenging. The British Medical Association highlights three key ethical considerations for elective students Conclusion: Prospective elective students would benefit from pre‐departure training on self‐assessment of competency and cultural awareness. UK medical schools have an ethical duty to encourage students to consider the impact of their elective placements on host institutions.